(untitled) (Indian Journal of Animal Production and Management, 2024)
The purpose of the study was to investigate the effects of supplementing lemongrass (Cymbopogon citratus) and sweet orange peel (Citrus sinensis) powder on the growth performance of Uttara chicken. A total of 160-day-old Uttara chicks were randomly divided into four treatment groups, each consisting of 40 chicks with four replicates per treatment. The chickens were fed different diets: a control diet in treatment T0, 0.5% lemongrass powder in treatment T1, 0.5% sweet orange peel powder in treatment T2, and a combination of 0.5% lemongrass powder and 0.5% sweet orange peel powder in treatment T3. The feeding trial lasted for 12 weeks. The results indicated that the overall body weight gain of birds in the 1004.08 g (T2) group was significantly higher compared to 907.57 g (T0), 927.12 g (T1), and 882.08 g (T3). The feed intake was not affected by either supplementing lemongrass or sweet orange peel powder in feed. Furthermore, the results indicated that the overall feed conversion ratio of birds in the 2.86 (T2) group was significantly better compared to 3.16 (T0), 3.10 (T1), and 3.26 (T3). The study concluded that supplementing with sweet orange peel (T2) had beneficial effects on body weight gain and FCR in Uttara chickens, suggesting its use as a feed supplement for improved profitability.